2013
DOI: 10.3389/fpsyg.2013.00461
|View full text |Cite
|
Sign up to set email alerts
|

Judgment of emotional information expressed by prosody and semantics in patients with unipolar depression

Abstract: It was the aim of this study to investigate the impact of major depressive disorder (MDD) on judgment of emotions expressed at the verbal (semantic content) and non-verbal (prosody) level and to assess whether evaluation of verbal content correlate with self-ratings of depression-related symptoms as assessed by Beck Depression Inventory (BDI). We presented positive, neutral, and negative words spoken in happy, neutral, and angry prosody to 23 MDD patients and 22 healthy controls (HC) matched for age, sex, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 59 publications
5
29
1
Order By: Relevance
“…Moreover, MDD patients pay less attention to happy faces (Duque & Vázquez, ), classify them more frequently as neutral (Gur et al, ; Surguladze et al, ), and perceive them as less intensive (Joormann & Gotlib, ; Yoon, Joormann, & Gotlib, ) than HC. Analogous to results in the facial domain, studies on perception of emotional prosody revealed a negative bias of MDD patients for ambiguous stimuli (Kan, Mimura, Kamijima, & Kawamura, ) and reduced perception of positive prosody (Liu, Wang, Zhao, Ning, & Chan, ; Schlipf et al, ). Neuroimaging studies in healthy subjects demonstrated that the middle part of the right superior temporal gyrus (STG; Ethofer et al, ; Ethofer, Van De Ville, Scherer, & Vuilleumier, ; Grandjean et al, ; Wiethoff et al, ) as well as the amygdala (Fecteau, Belin, Joanette, & Armony, ; Frühholz et al, 2011; Liebenthal, Silbersweig, & Stern, ; Wiethoff, Wildgruber, Grodd, & Ethofer, ) show enhanced reactivity to emotional prosody and thus represent key areas within the network involved in affective sound processing (Frühholz, Trost, & Kotz, ).…”
Section: Introductionmentioning
confidence: 80%
“…Moreover, MDD patients pay less attention to happy faces (Duque & Vázquez, ), classify them more frequently as neutral (Gur et al, ; Surguladze et al, ), and perceive them as less intensive (Joormann & Gotlib, ; Yoon, Joormann, & Gotlib, ) than HC. Analogous to results in the facial domain, studies on perception of emotional prosody revealed a negative bias of MDD patients for ambiguous stimuli (Kan, Mimura, Kamijima, & Kawamura, ) and reduced perception of positive prosody (Liu, Wang, Zhao, Ning, & Chan, ; Schlipf et al, ). Neuroimaging studies in healthy subjects demonstrated that the middle part of the right superior temporal gyrus (STG; Ethofer et al, ; Ethofer, Van De Ville, Scherer, & Vuilleumier, ; Grandjean et al, ; Wiethoff et al, ) as well as the amygdala (Fecteau, Belin, Joanette, & Armony, ; Frühholz et al, 2011; Liebenthal, Silbersweig, & Stern, ; Wiethoff, Wildgruber, Grodd, & Ethofer, ) show enhanced reactivity to emotional prosody and thus represent key areas within the network involved in affective sound processing (Frühholz, Trost, & Kotz, ).…”
Section: Introductionmentioning
confidence: 80%
“…Kan et al (2004) exploiting mute video and audio recordings found a poorer decoding accuracy of surprise for the audio stimuli. Schlipf et al (2013) reported that depressed subjects are impaired in processing positive emotional words exploiting a set of emotional adjectives (of positive, negative, and neutral valence) administered through speech vocal presentation.…”
Section: Resultsmentioning
confidence: 99%
“…This states that it is a universal and innate human ability to recognize the facial expressions corresponding to the six emotions called basic or primary (happiness, surprise, disgust, sadness, fear, and anger). The effectiveness of people with depression in decoding emotional expressions through photos was investigated with several methodologies, including the morphing task (Bediou et al, 2005;Joormann and Gotlib, 2006;Gilboa-Schechtman et al, 2008;LeMoult et al, 2009;Schaefer et al, 2010;Aldinger et al, 2013), the emotion recognition task (Kan et al, 2004;Leppänen et al, 2004;Gollan et al, 2008Gollan et al, , 2010Uekermann et al, 2008;Wright et al, 2009;Douglas and Porter, 2010;Milders et al, 2010;Naranjo et al, 2011;Punkanen et al, 2011;Péron et al, 2011;Watters and Williams, 2011;Schneider et al, 2012;Schlipf et al, 2013;Chen et al, 2014), the emotion attentional task (Gotlib et al, 2004;Joormann and Gotlib, 2007;Leyman et al, 2007;Kellough et al, 2008;Sanchez et al, 2013;Duque and Vázquez, 2014), the matching task (Milders et al, 2010;Liu et al, 2012;Chen et al, 2014), and the dot-probe detection task (Fritzsche et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was both found that depressed subjects are slow and less accurate [1,3,10,12,14,20,34,41], as well as, fast and more accurate in decoding negative emotions [25,26,28,39]. In general, it was found that depressed subjects may exhibit a global deficit in decoding emotions [4,18,31] and be less accurate than healthy subjects in decoding happiness [21,23,24,27,35,37]. Since all the above results were obtained exploiting mostly static stimuli and/or only one communication mode (only audio or only video), the goal of the present study is to investigate on the ability of depressed patients to decode emotional multimodal dynamic stimuli.…”
Section: Introductionmentioning
confidence: 93%